Textural changes of graphitic carbon by tectonic and hydrothermal processes in an active plate boundary fault zone, Alpine Fault, New Zealand - Kirilova, M.; Toy, V.; Timms, Nicholas Eric; Halfpenny, A.; Menzies, C.; Craw, D.; Beyssac, O.; Sutherland, R.; Townend, J.; Boulton, C.; Carpenter, B.; Cooper, A.; et al. (Geological Society Publishing House, 2018)
Graphitization in fault zones is associated both with fault weakening and orogenic gold mineralization. We examine processes of graphitic carbon emplacement and deformation in the active Alpine Fault Zone, New Zealand by analysing samples obtained from Deep Fault Drilling Project (DFDP) boreholes. Optical and scanning electron microscopy reveal a microtextural record of graphite mobilization as a function of temperature and ductile then brittle shear strain. Raman spectroscopy allowed interpretation of the degree of graphite crystallinity, which reflects both thermal and mechanical processes. In the amphibolite-facies Alpine Schist, highly crystalline graphite, indicating peak metamorphic temperatures up to 640°C, occurs mainly on grain boundaries within quartzo-feldspathic domains. The subsequent mylonitization process resulted in the reworking of graphite under lower temperature conditions (500-600°C), resulting in clustered (in protomylonites) and foliation-aligned graphite (in mylonites). In cataclasites, derived from the mylonitized schists, graphite is most abundant ( < 50% as opposed to < 10% elsewhere), and has two different habits: inherited mylonitic graphite and less mature patches of potentially hydrothermal graphitic carbon. Tectonic-hydrothermal fluid flow was probably important in graphite deposition throughout the examined rock sequences. The increasing abundance of graphite towards the fault zone core may be a significant source of strain localization, allowing fault weakening.